The Persuadable Voter : Wedge Issues in Presidential Campaigns - Hillygus, D. Sunshine (Book collections on Project MUSE., 2014)
The use of wedge issues such as abortion, gay marriage, and immigration has become standard political strategy in contemporary presidential campaigns. Why do candidates use such divisive appeals? Who in the electorate is persuaded by these controversial issues? And what are the consequences for American democracy? In this provocative and engaging analysis of presidential campaigns, Sunshine Hillygus and Todd Shields identify the types of citizens responsive to campaign information, the reasons they are responsive, and the tactics candidates use to sway these pivotal voters. The Persuadable Vo.